2015
DOI: 10.1128/mbio.00660-15
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cell Enlargement Requires Control of Cell Wall Stiffness Mediated by Peptidoglycan Hydrolases

Abstract: Most bacterial cells are enclosed in a single macromolecule of the cell wall polymer, peptidoglycan, which is required for shape determination and maintenance of viability, while peptidoglycan biosynthesis is an important antibiotic target. It is hypothesized that cellular enlargement requires regional expansion of the cell wall through coordinated insertion and hydrolysis of peptidoglycan. Here, a group of (apparent glucosaminidase) peptidoglycan hydrolases are identified that are together required for cell e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 44 publications
4
118
0
Order By: Relevance
“…Protein synthesis inhibitors induce cell wall thickening by stopping enlargement of the cell wall surface [188,189], possibly by inhibiting synthesis of the peptidoglycan hydrolases needed to loosen the expanding walls [189,194]. This, in the absence of any accompanying decrease in synthesis or incorporation of peptidoglycan precursor, leads to thickening of the existing cell wall [188].…”
Section: Peptidoglycan Thickeningmentioning
confidence: 99%
“…Protein synthesis inhibitors induce cell wall thickening by stopping enlargement of the cell wall surface [188,189], possibly by inhibiting synthesis of the peptidoglycan hydrolases needed to loosen the expanding walls [189,194]. This, in the absence of any accompanying decrease in synthesis or incorporation of peptidoglycan precursor, leads to thickening of the existing cell wall [188].…”
Section: Peptidoglycan Thickeningmentioning
confidence: 99%
“…These data suggest that although Atl, SagA, and ScaH exhibit roles distinctive from the role of SagB, further genetic loss of glucosaminidase activity aggravates the sagB mutant phenotype. Of note, Wheeler and colleagues, studying S. aureus SH1000, a laboratory strain, reported that expression of glucosaminidase was essential for S. aureus growth and that this requirement was mostly dependent on sagB (36). Changes in the structure of the cell envelope have been described to affect bacterial susceptibility to antibiotics (50).…”
Section: N-acetylglucosaminidases Of Staphylococcus Aureus Newmanmentioning
confidence: 99%
“…aureus Newman variants lacking four glucosaminidase genesatl, sagAB, and scaH-are viable and, compared to the wild type, replicate at a slightly reduced rate. In contrast, the S. aureus SH1000 atl sagA scaH mutant cannot replicate without sagB expression (36). Unlike SH1000, a laboratory strain that has been cured of bacteriophages (36), S. aureus Newman is lysogenized by four different phages, two of which encode muralytic enzymes with predicted N-acetylglucosaminidase activity (Fig.…”
Section: Fig 10mentioning
confidence: 99%
See 2 more Smart Citations